Prevalence and factors associated with frailty among elderly in central Rajasthan: A cross-sectional study - Gaurav Meratwal; Ruchita Banseria; Mahendra Khanna; Ashok Kumar (Elsevier, 2023)
Background: Frailty increases the risk of disability, falls, cognitive decline, hospitalisation, dependency, and mortality in older adults. The study aimed to find out the prevalence and associated factors of frailty among the elderly using Field's physical constructs of frailty. Methods: It was a hospital-based cross-sectional study, conducted in a tertiary care hospital in central Rajasthan, from May 2022 to October 2022. Data were collected from 288 participants. Categorical data were presented as proportion, and continuous data were presented as mean (SD). The Chi-square test and multivariate logistic regression were used to find out the association between frailty and other variables. Results: About one-third (32.3%) of participants were frail, 32.3% were pre-frail, and 35.4% were robust. In multivariate analysis, frailty was found more in the participants who were not in union than those who were in union (aOR = 3.62, p = 0.001). It was more in sedentary persons (aOR = 13.54, p < 0.01) and persons with some physical activity (aOR = 4.39, p = 0.003) than the persons with strenuous physical activity levels. The prevalence of frailty was also associated with morbidity (aOR = 5.84, p < 0.01); and with a history of falls (aOR = 2.67, p = 0.003). Conclusion: Nearly one third elderly population is frail and one third is prefrail. The growing older population and the corresponding increase in the prevalence of frailty would have a significant negative impact on the already overburdened health services. Community-based interventions should be developed and incorporated to avert and mitigate the effects of frailty.